Katalog der in den Sammlungen des ehemaligen Deutschen Entomologischen Institutes aufbewahrten Typen - VI (Homoptera (exklusive Aphidina)). - Gaedike, Hannelore (Contributions to Entomology = Beiträge zur Entomologie, 1971)
There is presented a catalogue of type specimens of Homoptera (exklusive Aphidina) preserved in the collections of the former Deutsches Entomologisches Institut.Nomenclatural Actsesox Breddin, 321 (Capnodistes), Lectotypetrucidula Breddin, 1903 (Conogonia), Lectotypeaglaie Breddin, 1902 (Cosmoscarta), Lectotypearethusa Breddin, 1900 (Cosmoscarta), Lectotypebriseis Breddin, 1903 (Cosmoscarta), Lectotypecallirrhoe Breddin, 1901 (Cosmoscarta), Lectotypecassandra Breddin, 1903 (Cosmoscarta), Lectotypechryseis Breddin, 1903 (Cosmoscarta), Lectotypeclematie Breddin, 1901 (Cosmoscarta), Lectotypecrocale Breddin, 1902 (Cosmoscarta), Lectotypecyane Breddin, 1900 (Cosmoscarta), Lectotypeerato Breddin, 1903 (Cosmoscarta), Lectotypehecate Breddin, 1903 (Cosmoscarta), Lectotypehippodamia Breddin, 1903 (Cosmoscarta), Lectotypehyale Breddin, 1901 (Cosmoscarta), Lectotypehyphinoe Breddin, 1902 (Cosmoscarta), Lectotypephiale Breddin, 1902 (Cosmoscarta), Lectotypepirene Breddin, 1900 (Cosmoscarta), Lectotypeprogne Breddin, 1903 (Cosmoscarta), Lectotypepsecas Breddin, 1901 (Cosmoscarta), Lectotypesanguiniflua Breddin, 1899 (Cosmoscarta), Lectotypechlorizans Breddin, 1902 (Ennya), Lectotypefairmairei Breddin, 1902 (Ennya), Lectotypeeos Breddin, 1902 (Eoscarta), Lectotypeliternoides Breddin, 1902 (Eoscarta), Lectotypevulpeculus Breddin, 1901 (Gargara), Lectotypeeos Breddin, 1901 (Huechys), Lectotypeforcipata Breddin, 1901 (Mioscarta), Lectotypevitreolimbata Breddin, 1905 (Platypleura), Lectotypesarasinorum Breddin, 1901 (Pyrgauchenia), Lectotypefoersteri Breddin, 1902 (Pyrgophyllium), Lectotypewallacei Breddin, 1902 (Pyrgophyllium), Lectotypelocomotiva Breddin, 1901 (Sphongophorus), Lectotypemachinula Breddin, 1901 (Sphongophorus), Lectotypeaurorula Breddin, 1901 (Tettigonia), Lectotypecentrivittata Breddin, 1899 (Tettigonia), Lectotypeincula Breddin, 1901 (Tettigonia), Lectotypematutinula Breddin, 1903 (Tettigonia), Lectotypemorosula Breddin, 1903 (Tettigonia), Lectotypenitidula Breddin, 1902 (Tettigoscarta), Lectotype